2020
DOI: 10.3892/mmr.2020.11248
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of circular RNAs and their potential role in early‑stage diabetic cardiomyopathy

Abstract: diabetic cardiomyopathy (dcM) is a severe cardiovascular complication of diabetes mellitus (dM). detecting dcM during the early stages of the disease remains a challenge, as the molecular mechanisms underlying early-stage dcM are not clearly understood. circular rna (circrna), a type of non-coding RNA, has been confirmed to be associated with numerous diseases. However, it is still unclear how circrnas are involved in early-stage dcM. in the present study, heart tissues harvested from BKS-db/db knockout mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Other circular RNAs, altered in diabetic retinopathy include circular DNMT3B and circRNA_0084043, each working through various pathways 24 , 25 . In the heart, 58 significantly differentially expressed circRNAs were identified in db/db mice, a model of type 2 diabetes 26 . Also identified are alterations of circRNA_010567 and circRNA_000203 working through various pathways to regulate specific transcript altering fibrosis related genes 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Other circular RNAs, altered in diabetic retinopathy include circular DNMT3B and circRNA_0084043, each working through various pathways 24 , 25 . In the heart, 58 significantly differentially expressed circRNAs were identified in db/db mice, a model of type 2 diabetes 26 . Also identified are alterations of circRNA_010567 and circRNA_000203 working through various pathways to regulate specific transcript altering fibrosis related genes 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific pathway has yet to be further verified. 147 Furthermore, Yang et al 148 Although research on circRNAs in CVDs is just emerging when compared with other research fields, such as cancer and neurological disorders, multiple studies have confirmed that circRNAs with stable, highly conserved and longer half-lives have bright prospects as candidate biomarkers and treatment targets for CVDs.…”
Section: Diab E Tic C Ardiomyopathymentioning
confidence: 99%
“…Subsequent functional analysis indicated that these differentially expressed circRNAs and their target mRNAs were mainly involved in the regulatory pathways of glycolipid metabolism. However, the specific pathway has yet to be further verified 147 . Furthermore, Yang et al 148 found that hsa_circ_0076631, a novel circRNA named caspase‐1‐associated circRNA (CACR), was significantly elevated in both DCM cardiomyocytes and the serum of diabetic patients.…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…Dong et al [ 107 ] carried out high-throughput RNA sequencing on the myocardium of a mouse model in order to identify circRNA expression. They determined that 58 circRNAs were markedly differentially expressed.…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%